Unusual uses and experiences are good for feeling insightful, but not for problem solving: contributions of schizotypy, divergent thinking, and fluid reasoning, to insight moments. Issue 6 (3rd October 2021) - Webb, Margaret E.; Little, Daniel R.; Cropper, Simon J.
ABSTRACT: The current paper investigates the individual differences underlying the ability to solve classic and contemporary insight problems along the subjective phenomenology of insight in the solution of these problems. We investigate fluid reasoning, divergent thinking and schizotypy. Experiments 1–3 (total N  = 434) investigated the association between schizotypy, divergent thinking, reasoning abilities, and participants' tendencies to report feelings associated with insight (e.g. aha experience) in the solution of classic insight, classic non-insight problems, and compound remote associates. We found that both positive schizotypy (particularly the subscale Unusual Experiences) and originality (uncommon responses in a creativity task) were positive predictors of aha experiences, though not of problem solving. These results highlight important individual differences in the tendency to perceive meaning in problem solving and the implications for our metacognitive judgments of truth in our problem-solving processes.